(untitled) (Psicologia USP, 1993)
This paper analyses the theoretical foundations and the practical potentialities for teacher education based on interpretations of autobiographies and of narratives about intelectual formation. It discusses theoretical issues related to individual and collective memory, to traditional processes of teacher education, and to studies about gender, particularly about women's condition and school work. It also brings to light and analyses the fruitfulness of the proposal for the formation of a professional counter-memory, by means of the study of autobiographies and narratives, in the process of extended formation of teachers.